Efek Media Audio Visual Berbasis Video Animasi Terhadap Kemampuan Membaca Permulaan Anak Usia Dini - Alfadillah, Tri; Syamsuardi, Syamsuardi; Amal, Azizah (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2025)
This research is motivated by the fact that the early numeracy skills of children in Group A are still less than optimal, and teachers have not yet implemented enjoyable learning methods. Therefore, the researcher conducted a study on improving early numeracy skills through intriguing and enjoyable learning that can be repeated, one of which is the use of the number block method. The purpose of this study was to enhance early numeracy skills in children from Group A. This research used a descriptive method with a qualitative approach. The subjects of the study were 15 group A children. Data were collected through interviews, observation, and documentation. The data analysis technique used qualitative analysis, consisting of data reduction, data display, and conclusion drawing or verification. Based on the results of the study, the use of Numberblocks media was able to improve children's early numeracy skills over the course of eight meetings. The results showed that eight children demonstrated very good development, 4 children developed as expected, and three children still required guidance from the teacher. During these activities, the children were able to meet four indicators of early numeracy skill development. These findings indicate that the use of number block media is effective in enhancing the early numeracy skills of group A children at Little Smart Kindergarten in Bandung City. Moreover, this approach can stimulate children's interest in thinking and encourage active participation in learning.